Assessment of Knowledge and Attitude Among College Students Toward Umbilical Cord Blood and its Banking - Yadav, Namita; D'Souza, Vita Leena; Geethamani, T. (Nepal Journal of Health Sciences, 2021)
Introduction: Umbilical cord blood (UCB) is a good source of haematopoietic stem cells and progenitor cells. UCB stem cells are used in treatment of a variety of blood and bone marrow diseases, blood cancers, metabolic disorders and immune deficiencies.Objective: This study aimed in investigating college students’ knowledge and attitude about UCB and UCB banking.Methods: It is a descriptive cross-sectional study. The study was conducted in East West College of Management, Bangalore, India from September 2018 to August 2019. A total 80 college students were selected by random sampling techniques. There were self-structured questionnaires used to assess the knowledge and attitude regarding UCB and UCB banking. The data analysis was done using descriptive and inferential statistics in SPSS version 21.Results: The maximum number of participants were from age group 19-21 years followed by age group 16-18 years. The overall knowledge score was 21.05±5.11 with mean percentage score of 60.14. The 71.25% (57) of subjects had moderately adequate knowledge; whereas, 25% (20) of subjects showed adequate knowledge. Similarly, the overall attitude score of subjects was 61.5±5.17 with a mean percentage score of 51.25%. Out of the total participants, 90% (72) had neutral attitude, 10% (8) exhibited positive attitude and none of the subjects exhibited negative attitude towards UCB banking. There was no association found between knowledge and sociodemographic variables and between attitude and sociodemographic variables.Conclusion: The majority of the respondents had moderate knowledge and maximum had neutral attitude on umbilical cord blood and umbilical cord blood banking.